2017
DOI: 10.1097/ta.0000000000001516
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of prehospital triage protocols in selecting severely injured patients

Abstract: Systematic review, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 50 publications
3
92
0
1
Order By: Relevance
“…42 However, the model is a significant improvement compared with the existing protocols. 5,6,16,43 Whether further improvement of undertriage is achievable by solely improving the protocol is unclear. Previous studies have shown that addition of the judgment of EMS professionals can be useful in the identification of severely injured patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 However, the model is a significant improvement compared with the existing protocols. 5,6,16,43 Whether further improvement of undertriage is achievable by solely improving the protocol is unclear. Previous studies have shown that addition of the judgment of EMS professionals can be useful in the identification of severely injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, an ISS greater than 15 is the most used surrogate marker for a severely injured patient when evaluating prehospital trauma triage; therefore, we chose this variable to define a severely injured patient. 5…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, only a minority of the severely injured patients were identified by the triage protocol. A recent literature review showed that on a worldwide scale, the different triage protocols are not capable to accurately discriminate between patients with and without severe injuries [14]. Thus, efforts to improve the triage protocol are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Prehospital trauma triage protocols have been studied extensively over the past decades [11][12][13][14]. However, it is currently unknown what factors are associated with EMS provider judgment and to what extent compliance to the triage protocol influences quality of prehospital trauma triage.…”
Section: Introductionmentioning
confidence: 99%